An interactive web demo for various cipher mode operations - Muhammad Hanif Abd Latif (2019)
The objective of this project is to build an interactive web-based application to cater for various block ciphers. The focus is also to study the algorithms, modes and to provide a learning tool or application for education. The web-application will focus mainly on AES, DES and Blowfish algorithm that are commonly used. The web-application is to showcase how the block cipher in these algorithms would perform with the various arbitrary user inputs through a flexible selection of the different modes of operations. As such, the web-application also aims to provide an easy and user-friendly environment to users for seamless navigation, therefore the web-application will be built with a responsive UI/UX that provides usability to both mobile phones and computers. Thus, enables users to expand their knowledge in learning about block ciphers in an enriching platform.